THE ASPERGER SYNDROME IN ALAN TURING CHARACTER ON THE IMITATION GAME FILM - Silvia Erlin Aditya S; noti Aprianti (Literary Criticism, 2018)
The aims of the study is to analyze the Asperger syndrome in Alan Turing character on The Imitation Game film. This research has two objectives: first, to describe the characteristic of the Asperger Syndrome in Alan Turing character on The Imitation Game film. Second, to reveal the verbal language problems of the Asperger Syndrome in Alan Turing character on The Imitation Game film. This research employed a descriptive qualitative method. It is concerned with the description of the data in the form of conversation on The Imitation Game film based on Tony Attwood theories of characteristic and verbal language problems of Asperger syndrome. Based on the obtained result, it can be concluded that Asperger Syndrome is the dominant characteristic of Alan Turing character in The Imitation Game film namely the difficulties communication and the controlling of emotions. While the minimal characteristics are difficulties a making friends and often teased by other children. And then, the dominant types of verbal language problems found is the literal interpretation. Keywords : Alan Turing , Asperger Syndrome, Film, The Imitation Game